Social media policies at US medical schools - Kind, Terry (Medical Education Online, 2010)
BACKGROUND/PURPOSE: Today's medical students are learning in a social media era in which patient confidentiality is at risk yet schools’ social media policies have not been elucidated. The purpose of this study is to describe the presence of medical schools on top social media sites and to identify whether student policies for these schools explicitly address social media use. METHOD: Websites of all 132 accredited US medical schools were independently assessed by two investigators for their presence (as of March 31, 2010) on the most common social networking and microblogging sites (Facebook and Twitter) and their publicly available policies addressing online social networking. Key features from these policies are described. RESULTS: 100% (n=132) of US medical schools had websites and 95.45% (126/132) had any Facebook presence. 25.76% (34/132) had official medical school pages, 71.21% (94/132) had student groups, and 54.55% (72/132) had alumni groups on Facebook. 10.6% of medical schools (14/132) had Twitter accounts. 128 of 132 medical schools (96.97%) had student guidelines or policies publicly available online. 13 of these 128 schools (10.16%) had guidelines/policies explicitly mentioning social media. 38.46% (5/13) of these guidelines included statements that defined what is forbidden, inappropriate, or impermissible under any circumstances, or mentioned strongly discouraged online behaviors. 53.85% (7/13) encouraged thoughtful and responsible social media use. CONCLUSIONS: Medical schools and their students are using social media. Almost all US medical schools have a Facebook presence, yet most do not have policies addressing student online social networking behavior. While social media use rises, policy informing appropriate conduct in medical schools lags behind. Established policies at some medical schools can provide a blueprint for others to adopt and adapt.